Reconceptualizing Consumer Responsibility: From Rosters to Philosophy - McGregor, Sue (ETHICS IN PROGRESS, 2025)
Conceptual papers reflect a researcher’s theoretical thoughts and philosophical speculations about a topic and are especially useful for generating ideas that incentivize theory development. This conceptual paper shares a philosophical reconceptualization of consumer responsibility, which people traditionally approach using rosters of corresponding responsibilities and rights. After profiling rosters from both the United Nations and Consumers International, the consumer responsibility phenomenon was reconceptualized through three philosophical queries: (a) what is it to be responsible (moral reasoning, feelings, or virtue/character trait); (b) what is a person responsible for (past and future orientation — retrospection and prospection); and (c) before whom is someone responsible (self-attribution versus diffusion)? Future researchers are encouraged to use this new conceptual framework to study and theorize the different ways people might philosophically understand being responsible consumers.